TEACHING ENGLISH ON THE BASIS OF A COLLABORATIVE APPROACH - Davurova Soxiba Usanboyevna (International Scientific and Current Research Conferences, 2023)
The collaborative approach in teaching English has gained significant attention in recent years due to its potential to enhance language acquisition and foster meaningful interactions among learners. This article explores the theoretical foundations, benefits, and effective strategies associated with employing a collaborative approach in teaching English. By examining relevant research and practical applications, this article aims to provide insights for educators and learners seeking to optimize the language learning process.